Jesus doesn't care about your messy house : he cares about your heart - White, Dana K. (W Publishing Group, an imprint of Thomas Nelson, 2025)
This book is for you, if no matter how competent you feel in other parts of your life, you still feel overwhelmed and defeated by your messy home. While it's true that keeping a clean and organized living space can contribute to a sense of peace and well-being, it should never be equated with your worth, moral standing, or what Jesus thinks about you.